(untitled) (TEL Tempo, Espaço e Linguagem, 2021)
Through a Marxist approach, the purpose of this article is to analyse if and how The grapes of wrath (STEINBECK, 1939) articulates a perspective upon work and workers’ alienation. Having said that, while the specific context of this research is the novel itself, the overall context is the Great Depression, the greatest financial crises of U.S.A. history. The relationship between land, men, and capital, as it is developed by the narrative, is brought to the analysis. Taking the literary piece as the product of its culture, but also as producer of a new culture, my aim is to understand if and how a Marxist lens contributes to the reading of The grapes of wrath (STEINBECK, 1939), not as a token of reality, but as a glimpse to possibilities of realities other than that. Indeed, without objectively manifesting any ideological stance regarding the Great Depression, the findings of this research indicate how the narrative of social revolution is built within the story. Tougher and sadder than before, the Joad family is a picture of any proletarian family, living by instinct and accepting their fate only because everything they do in order to fight it never seems to work at all.